The United States Foreign Intervention and African Command (AFRICOM): Implications for Nigeria - Hakeem Olatunji Tijani (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
United States African Command is a unified combatant, which means that it combines both civilian and military functions with its area of responsibility totally dedicated to Africa. Putting the civilian functions such as aids, building of schools and other civil functions hitherto performed by such agencies as USAID and State Department into the operational obligations of Department of Defence suggests that AFRICOM’s utilitarian value in terms of its benefits to Nigeria is nil. Nigeria cannot benefit from AFRICOM. This is because AFRICOM is militarily structured with less capability to deal with issues of development in Nigeria. As a result of this, Nigeria should see AFRICOM as an extension of the American foreign policy of militarism. This paper considers that Nigeria should not accommodate AFRICOM on its territory. The theory that AFRICOM would bring cooperation between America and African countries on one hand and between Nigeria and America on the other is a hoax as far as difficulties of cooperation in international politics are concerned. Such impediments as the Problem of cheating, Problem of relative gains, Problem of absolute gains and Problem of interdependence are distinct quandary to cooperation between United States and Nigeria. The assumed cooperation is a unidirectional relationship that will tend towards favouring America and creating problems for Nigeria. Such problems include the recycling of terrorism in Nigeria and encircling Nigeria with terrorists. Intuitively, in an era of globalization, national governments do not have much influence in shaping their own destiny. In this light, therefore, Nigeria needs to refocus its external relations within the context of globalization.